Hubungan antara Perhatian yang Diberikan Orang Tua dengan Tingkat Perkembangan Moral Anak Usia Dini - Puput Melati; Setiawati Setiawati; Solfema Solfema (Universitas Negeri Padang, 2018)
Level moral development in early childhood in Kenagarian Lunang Barat, Kecamatan Lunang, Kabupaten Pesisir Selatan is still low category. This is allegedly due to the low attention give by parents. This study aims to reveal a picture of the attention given by parents to children, a picture of the level of early childhood moral development and the relationship between the two variables. This research is correlational research, with population and sampled are parent. Sampling with area random sampling technique. Tools for data collection used in the form of questionnaires and data analysis technique using the formula percentage and product moment formula. The results of the study include: (1) Attention given by the parents is still low category. (2) The level of early childhood moral development is still low category. (3) There is a significant relationship between the attention given to parents and the level of early childhood moral development. The suggestions in this study are that parents need to improve understanding, knowledge, and increase attention to children, so that children can show the good level of moral development.